2018
DOI: 10.1016/j.scitotenv.2018.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of cheese production: A case study of a small-scale factory in southern Europe and global overview of carbon footprint

Abstract: The environmental performance of a small-scale cheese factory sited in a NW Spanish region has been analysed by Life Cycle Assessment (LCA) as representative of numerous cheese traditional factories that are scattered through the European Union, especially in the southern countries. Inventory data were directly obtained from this facility corresponding to one-year operation, and the main subsystems involved in cheese production were included, i.e. raw materials, water, electricity, energy, cleaning products, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
(47 reference statements)
2
16
0
1
Order By: Relevance
“…Relating to water use and pollution, grazing appears to be the most impactful phase, with the exception of water depletion, for which the milking phase is the most unsustainable. Canellada et al (73) found similar results in their study, evidencing that milk production in small-scale cheese factories affects marine eutrophication, freshwater and marine ecotoxicity. Furthermore, Nemecek and Alig (71) described the environmental efficacy of low-input mountain production scenarios, producing results comparable to ours in terms of acidification, eutrophication potentials and resource consumption.…”
Section: Environmental Implicationssupporting
confidence: 73%
“…Relating to water use and pollution, grazing appears to be the most impactful phase, with the exception of water depletion, for which the milking phase is the most unsustainable. Canellada et al (73) found similar results in their study, evidencing that milk production in small-scale cheese factories affects marine eutrophication, freshwater and marine ecotoxicity. Furthermore, Nemecek and Alig (71) described the environmental efficacy of low-input mountain production scenarios, producing results comparable to ours in terms of acidification, eutrophication potentials and resource consumption.…”
Section: Environmental Implicationssupporting
confidence: 73%
“…Water-Energy-Food Nexus (Del Borghi et al 2020). Several studies aimed at evaluating environmental consequences due to food production chain: fruit and grain farm (Ingrao et al 2015;Tricase et al 2018), processed foods (Canellada et al 2018;Del Borghi et al 2014;Ingrao et al 2018), seafood and meat (Hospido et al 2006;López-Andrés et al 2018). In this context, packaging is also considered to have an effective impact estimation (Del Borghi et al 2018;Strazza et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The green concept has gained importance as it facilitates more and more organizations in minimizing their environmental impacts. A plethora of literature has emphasized the impact of green methods such as LCA, EMS, design for environment (DFE), energy management system (EnMS), and 3R (reducing, reusing, and recycling) on environmental performance [18,[26][27][28][29]. These practices have positive outcomes in the form of conforming regulatory requirements, meeting customers' demands of environmental-friendly products, and achieving environmental certification [30].…”
Section: Green Approachmentioning
confidence: 99%